Beyond Rules and Sanctions: The Role of Tax Socialization in Strengthening MSME Tax Compliance - Benget Yakub; Dahlifah Dahlifah (Santoso Academy Network, 2026)
This study examines the effects of the tax accounting system, taxpayer awareness, and tax sanctions on MSME tax compliance, with tax socialization as a moderating variable. It addresses the persistent challenge of low tax compliance despite ongoing regulatory reforms and enforcement efforts. The novelty of this study lies in integrating tax socialization as a moderating mechanism that strengthens the relationships between the tax accounting system, taxpayer awareness, tax sanctions, and taxpayer compliance. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The sample consisted of MSME taxpayers registered at the West Jakarta Directorate General of Taxes who had actively submitted their Annual Tax Returns and met the purposive sampling criteria. The findings show that the tax accounting system, taxpayer awareness, and tax sanctions positively and significantly influence taxpayer compliance. Tax socialization further strengthens these relationships, emphasizing its role in encouraging voluntary compliance. These findings highlight the strategic importance of tax socialization beyond enforcement. Practically, the Directorate General of Taxes should strengthen tax education, expand digital tax assistance, enhance taxpayer awareness programs, and implement fair sanction policies to improve sustainable tax compliance among MSMEs.